First-Principles Calculations of the Electronic and Optical Properties of CH3NH3PbI3 for Photovoltaic Applications. (2018) - Ali, Ibrahim O.A.; Joubert, Daniel P.; Suleiman, Mohamed S.H.
Abstract: Since the first efficient solid-state perovskite solar cells were reported in 2012, rapid development of the organic-inorganic hybrid halide perovskites has been made, and a new era in optoelectronic and solar cells technologies has emerged. The unique attributes of these hybrid halide perovskites make them highly promising materials for various practical applications including high performance in converting solar energy into electrical power, with very recent results demonstrating a 20.1% efficiency. However, the electronic and optical properties of these materials at low temperature have not been investigated extensively. Herein we analyse the electronic and optical properties of methyl-ammonium lead iodide perovskite, CH3 NH3 PbI3, using density functional theory (DFT) and many-body perturbation theory (MBPT). The electronic band gap and energy bands of CH3 NH3 PbI3 have been investigated using different density functional approximations with and without the effect of the spin orbit-coupling (SOC). Depending on the calculation method, we predicted the band gap to be in the range from 0.46 eV to 2.66 eV. In order to obtain optical spectra, we carried out Bethe-Salpeter equation (BSE) calculations on top of non-self-consistent G0 W0 calculations. We have presented the absorption coefficient, refractive index and reflectivity to describe optical properties of the investigated material. The phase is found to be semi-conducting with a direct band gap in the visible range of the spectrum and strong optical absorption in the visible range.